State involvement in self-help housing: reflections from the Free State - Ntema, John; Marais, Lochner (University of the Free State, 2010)
When John Turner forwarded his theories on self-help housing, he emphasised the concept of dweller control and argued that the state should not be involved in housing construction processes. Although there was worldwide acknowledgement of his ideas, a large number of self-help programmes developed with a fair amount of state-involvement. South Africa’s self-help programme, called the People’s Housing Process, is no exception in this respect. Although designed to ensure larger degrees of ownership by people, evidence of large-scale government influence is clear. This article assesses the application of self-help housing in the Free State province and argues that a technocratic rather than a people-centred approach (envisaged in policy documents) dominated the People’s Housing Process. The levels of influence by local people in project design, project implementation and housing design remain low, and the housing outcomes do not differ much from the normal project subsidy approach.

Toe John Turner sy teorieë oor self-helpbehuising voorgestel het, het hy bewonerbeheer as konsep beklemtoon en aan die hand gedoen dat die staat nie betrokke behoort te wees by prosesse om behuising op te rig nie. Hoewel sy gedagtes wêreldwye erkenning geniet het, het ’n groot hoeveelheid self-helpprogramme nietemin met ’n redelike mate van staatsbetrokkenheid ontwikkel. Suid-Afrika se self-helpprogram, genaamd die Behuisingsproses vir die Mense, is in hierdie verband geen uitsondering nie. Hoewel dit ontwerp is om ’n groter mate van eienaarskap by mense te verseker, is die getuienis van grootskaalse regeringsinvloed duidelik. Hierdie artikel beoordeel die toepassing van self-helpbehuising in die Vrystaat provinsie en argumenteer dat ’n tegnokratiese eerder as mensgesentreerde benadering die Behuisingsproses vir die Mense oorheers het. Die mate waartoe plaaslike mense ’n invloed in die projekontwerp, projekimplementering en behuisingontwerp kon uitoefen, bly laag en die behuisingsuitkomste verskil nie veel van die normale projeksubsidiebenadering nie.
Keywords: Self-help housing; Housing support